How Do Noninvasive Imaging Facilities Perceive the Accreditation Process? Results of an Intersocietal Accreditation Commission Survey - Manning, Warren J. (Clin Cardiol, 2015)
The Intersocietal Accreditation Commission (IAC) accredits vascular, echocardiography, nuclear medicine, computed tomography, and magnetic resonance imaging laboratories. How facilities involved in the accreditation process view accreditation is unknown. The objective of this study was to examine the perception of laboratory accreditation from those who had undergone the process. An electronic survey request was sent to all facilities that had received IAC accreditation at least once. Demographic information, as well as opinions on the perceived value of accreditation as it relates to 15 quality metrics was acquired. Responses were obtained from 2782 facilities. Of the 15 quality metrics examined, the process was perceived as leading to improvements by a majority of respondents for 10 (67%) metrics including: report standardization, adherence to guidelines, test standardization, report completeness, identification of deficiencies, improved staff knowledge, report timeliness, distinguished facility, correction of deficiencies, and image quality. Overall, the perceived improvement was greater for hospital‐based facilities (global 66% vs 59%; P < 0.001). Survey data demonstrate that the accreditation process has a positive perceived impact on the majority of examined metrics. These findings suggest that those undergoing the process find value in accreditation.